2016
DOI: 10.1055/s-0036-1585069
|View full text |Cite
|
Sign up to set email alerts
|

The Oblique Metaphyseal Shortening Osteotomy of the Distal Ulna: Surgical Technique and Results of Ten Patients

Abstract: Background Ulnocarpal abutment is a common condition following distal radius fractures. There are different surgical methods of treatment for this pathology: open and arthroscopic wafer procedure or an ulnar shortening osteotomy. We describe an oblique metaphyseal shortening osteotomy of the distal ulna using two cannulated headless compression screws. We report the results of 10 patients treated with this method. Materials and Methods Out of 17 patients, 10 could be reviewed retrospectively for this study. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…21,27,28,31 Various techniques for MUSO have been described. 8,21,27,31,42 In a biomechanical study of the closing wedge osteotomy technique at the distal ulnar metaphysis, Greenberg et al 33 demonstrated significant reductions in ulnar load in both static and dynamic phases of wrist motion without significant increases in transverse force across the DRUJ. The mean shortening achieved by the investigators was 2.8 mm in seven cadaver arms.…”
Section: Discussionmentioning
confidence: 99%
“…21,27,28,31 Various techniques for MUSO have been described. 8,21,27,31,42 In a biomechanical study of the closing wedge osteotomy technique at the distal ulnar metaphysis, Greenberg et al 33 demonstrated significant reductions in ulnar load in both static and dynamic phases of wrist motion without significant increases in transverse force across the DRUJ. The mean shortening achieved by the investigators was 2.8 mm in seven cadaver arms.…”
Section: Discussionmentioning
confidence: 99%
“…The contact area of both ends of V-shaped and trapezoidal osteotomy fractures is large, and the anti-rotation force is enhanced, but the operation is more complicated, the operation time is long, and the two ends of the fracture are prone to malalignment 9 . However, oblique osteotomy is easy to perform, with a large contact area and strong anti-rotation force, so it is widely used in the clinic 10 . Terzis et al 11 treated 17 patients with UIS with oblique USO and followed them up.…”
Section: Introductionmentioning
confidence: 99%
“…4 However, these studies often lacked patientreported outcome measures (PROMs), preoperative measurements, 5 or had a small sample size. [8][9][10] Our previous study on 106 patients found beneficial outcomes in patient-reported pain and function 12 months after USO, measured with the Patient-Rated Wrist and Hand Evaluation (PRWHE). 11,12 While shortterm outcomes are favourable, long-term PROMs beyond one year after USO are barely reported.…”
Section: Introductionmentioning
confidence: 99%
“… 4 However, these studies often lacked patient-reported outcome measures (PROMs), preoperative measurements, 5 or had a small sample size. 8 - 10 …”
Section: Introductionmentioning
confidence: 99%